A Hardware Implementation of an Online Frequency Dynamic Parameter Estimation - Chavez-Orostica, H; Quiroz-Moreno, J (Institute of Electrical and Electronics Engineers Inc., 2021)
The current concerns with inertia and frequency response deterioration have increased the interest in data analytics tools to assess the dynamic state of power systems. These assessments have emerged because of the increasing control room data availability in SCADA and synchrophasor networks. Additionally dynamic metrics and parameters have been proposed to assist power system dynamic operation. This work present an experimental implementation of an online tool to identify inertia and the time constants describing a reduced-order model of system frequency dynamics. The implementation shows empirical results in the Chilean Power System. © 2021 IEEE.